36.3k views
4 votes
How do I solve this?

How do I solve this?-example-1
User Kevin Bott
by
4.8k points

1 Answer

5 votes

Answer:

The equation of the required straight line is y = 4x + 1.

Explanation:

The equation of all the straight lines that are parallel to the straight line y = 4x - 3 is given by

y = 4x + c .............. (1)

where, c is any real constant and c ≠ - 3.

{Since parallel straight lines have the same slope and different y-intercept }

Now, we have to find the value of c such that the parallel straight line passes through the point (-1,-3).

Now, putting x = - 1 and y = - 3 in equation (1) we get,

- 3 = 4(- 1) + c

⇒ c = 1

Therefore, the equation of the required straight line is y = 4x + 1. (Answer)

User Dereck
by
5.5k points